Possible cosmic rays origin of periodic components in gamma-background signals - A. D. Skorbun (Âderna Fìzika ta Energetika)
Analysis of a long-term regular series of measurements of signals from the automated system of radiation control (ASRC) in the Chornobyl exclusion zone revealed many features, which are reproduced for different observation posts and which we will try to consider from the general position of the influence of cosmic factors. It is implied that these features are clearly linked to certain astronomical phenomena. It is possible to propose a model that describes all these phenomena, namely the possibility of manifestations of the influence of cosmic rays. Such a mechanism as a cause of changes in radioactive background signals in general and in ASRC signals, in particular, has not been considered previously. Probably because its contribution was considered small.